2020
DOI: 10.1177/2167702619894905
|View full text |Cite
|
Sign up to set email alerts
|

Informant Discrepancies in Judgments About Change During Mental Health Treatments

Abstract: Understanding how mental health treatments benefit people who receive treatment comes with a challenge: Often different people involved in treatment have different impressions of the treatment’s ultimate effects. How do people reconcile these different reports to understand the true benefit of treatment? In a series of four experiments, we tested people’s beliefs about how to integrate information from multiple informants for the treatment improvement of child clients. We found that laypeople (Experiments 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In practice, low informant convergence is often interpreted as reflecting informant bias or measurement error (De Los Reyes, 2011), which results in suboptimal use of these reports. Specifically, when confronted with informant discrepancies, clinicians often make decisions that “toss out” several informants’ reports in favor of a single informant’s report (Brown-Jacobsen et al, 2011; Hawley & Weisz, 2003; Marsh et al, 2020). Given this leaning to remove reports and the findings reported in this article, we suspect that one’s hypothesis about the meaning underlying informant discrepancies (e.g., they reflect measurement error, one informant provides “better” reports) might result in idiosyncratic decision-making for important clinical tasks such as diagnosis and treatment selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, low informant convergence is often interpreted as reflecting informant bias or measurement error (De Los Reyes, 2011), which results in suboptimal use of these reports. Specifically, when confronted with informant discrepancies, clinicians often make decisions that “toss out” several informants’ reports in favor of a single informant’s report (Brown-Jacobsen et al, 2011; Hawley & Weisz, 2003; Marsh et al, 2020). Given this leaning to remove reports and the findings reported in this article, we suspect that one’s hypothesis about the meaning underlying informant discrepancies (e.g., they reflect measurement error, one informant provides “better” reports) might result in idiosyncratic decision-making for important clinical tasks such as diagnosis and treatment selection.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, low correspondence often results in assessors shunning multi-informant approaches to assessment and instead making clinical decisions that rely on data from a single source (Loeber, Green, & Lahey, 1990; Loeber, Green, Lahey, & Stouthamer-Loeber, 1989; Marsh, Zeveney, & De Los Reyes, 2020). This practice likely reflects long-held assumptions that low informant correspondence signals measurement error or informant biases (De Los Reyes, 2011).…”
Section: Suboptimal Use Of Multi-informant Reports: a Clinical Decisimentioning
confidence: 99%
“…Although our results were obtained in a sample of general population rather than from doctors or medical experts, the literature on cognitive biases suggests that there is no reason to think that experts would behave differently (Neal et al, 2022 ) even in real situations (Frotvedt et al, 2020 ), particularly in certain conditions such as time pressure (Kelemen et al, 2013 ), which is a common situation for real-life medical decisions. Thus, similar cognitive factors influence decisions by novices and experts in the health area (Kim & Ahn, 2002 ; Marsh et al, 2016 , 2020 ), and sometimes experts can even show an exacerbated bias the longer they have been in the profession (Mamede et al, 2010 ). Moreover, this effect of previous knowledge has been also reported in the field of causal learning, actually inflating the very same type of illusion that we have reported in this paper (Yarritu & Matute, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent experimental study highlighted the complexity of dealing with discrepant reports in MHS. Marsh et al ( 57 ) conducted four experimental studies and showed that when faced with discrepant information, laypeople and MHS professionals choose to trust one of the informants. Additionally, the choice of whether to trust the client or the informant is based on the specific mental health condition (internalizing or externalizing), the relationship with the client (close or distant), and the nature of the report (optimism vs. pessimism).…”
Section: Discussionmentioning
confidence: 99%